IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN PENDIDIKAN KARAKTER DI MASA PANDEMI COVID-19 (Di SMA Negeri 1 Ketungau Hilir) - Darmawan Saputra; Purniadi Putra; Wulan Purnama Sari (Cross-border, 2021)
Research is motivated by the learning implementasi in schools that is felt to still not create an atmosphere in instilling character education. This makes students lack the expected character such as religious, honest and tolerant. Moreover, during the Covid-19 pandemic, in fact the learning process is carried out in several ways, namely those known as PJJ, namely distance learning, offline, which is an offline system, or online system that is in the network. This research uses qualitative method. Research location in SMA Negeri 1 Ketungau Hilir Kabupaten Sintang. Data collection is done by observation, interview, and documentation. Result of this study is a implementasi of islamic religious education learning during the covid-19 pandemic the implementation of learning has not carried out face-to-face learning, due to the Covid-19 pandemic. But the learning carried out by PJJ is Distance Or Offline Learning, which is outside the Network which is scheduled once a week when taking and collecting tasks. The character values instilled during the Covid-19 pandemic are Religious, Honest, and Tolerant Characters.